Navigating Succession in Post-Communistic Family Businesses : Beyond Motivations, Barriers, And Perceived Deficiencies of The Potential Successors - Greksová, Ester; Jurek, Martin; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Family business owners worldwide are grappling with a decline of intention of the next generation to assume role of a successor. Moreover, in post-communistic countries, the challenging transition from the first to the second generation has commenced, with generation Z on the brink of joining the successor pool. This thesis employs a qualitative approach, utilizing semi-structured interviews with potential successors, to investigate the factors influencing Generation Z’s intention towards family businesses in post-communistic context. The findings indicate that in this region, early proactive efforts to foster emotional connection to the family business, alignment with and respect for Generation Z's work-related priorities to avoid them seeking better prospects elsewhere, and the openness of family business owners to new ideas while being able to relinquish control, are crucial in securing the interest of potential successors. While taking into consideration the research limitations, the implementation of these insights holds the potential to enhance the viability of intergenerational succession within family businesses in post-communistic contexts.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses